Sterols and Stanols in Foods and Dietary Supplements Containing Added Phytosterols: A Collaborative Study. (1st April 2018) - Srigley, Cynthia T.; Hansen, Steven L.; Smith, Sean A.; Abraham, Anjalika; Bailey, Eileen; Chen, Xiang; Chooi, Soo Hui; Clement, Lisa M.; Dao, Michael; Fardin Kia, Ali Reza; Mitchell, Barb; Mogla, Mohit; et al.
Abstract: An international, multilaboratory collaborative study was carried out to evaluate the performance of Official Method Ce 12‐16 of the American Oil Chemists' Society (AOCS) for the determination of plant sterols and stanols, collectively referred to as phytosterols, in foods and dietary supplements containing added phytosterols and in the phytosterol food additive concentrates used to prepare such products. AOCS Official Method Ce 12‐16 involves the extraction of free sterols/stanols and saponified steryl/stanol esters followed by the gas chromatographic separation and flame ionization detection of phytosterol trimethylsilyl ether derivatives. A total of 14 laboratories from six countries successfully completed the analysis of collaborative samples of foods (e.g., baked goods, beverages, margarines; n = 9), dietary supplements ( n = 5), and phytosterol concentrates ( n = 4). Study results for the contents of total phytosterols (weight/weight) were 0.19–8.4% for foods, 8.7–49% for dietary supplements, and 57–97% for concentrates. AOCS Official Method Ce 12‐16 showed acceptable performance for total and individual phytosterols, indicating that this method was suitable for the determination of added phytosterols in a wide variety of market products and concentrates. AOCS Official Method Ce 12‐16 is appropriate for the determination of the five major phytosterols (i.e., campesterol, stigmasterol, β‐sitosterol, campestanol, and sitostanol) that are the subject of the United States Food and Drug Administration's health claim for phytosterols and the reduced risk of coronary heart disease.